In vitro biocompatibility of poly(vinylidene fluoride-trifluoroethylene)/barium titanate composite using cultures of human periodontal ligament fibroblasts and keratinocytes - Teixeira, L. N.; Crippa, G. E.; Trabuco, A. C.; Gimenes, R. [UNESP]; Zaghete, M. A. [UNESP]; Palioto, D. B.; de Oliveira, P. T.; Rosa, A. L.; Beloti, M. M. (Elsevier B.V., 2010)
The mm of this work was to evaluate the biocompatibility of poly(vinylidene fluoride-trifluoroethylene)/barium titanate (P(VDF-TrFE)/BT) membrane to be used in guided tissue regeneration (GTR) Fibroblasts from human periodontal ligament (hPDLF) and keratinocytes (SCC9) were plated on P(VDF-TrFE)/BT and polytetrafluorethylene membranes at a cell density of 20.000 cells well(-1) and Cultured for up to 21 days Cell morphology, adhesion and proliferation were evaluated in hPDLF and keratinocytes, while total protein content and alkaline phosphatase (ALP) activity were assayed only for hPDLF Using a higher cell density. real-time polymerase chain reaction (PCR) was performed to assess the expression of typical genes of hPDLF, such as periostin, PDLs17, S100A4 and fibromodulin, and key phenotypic markers of keratinocytes, including involucrin, keratins 1. 10 and 14 Expression of the apoptotic genes bax, bcl-2 and Survivin was evaluated for both cultures hPDLF adhered and spread more oil P(VDF-TrFE)/BT, whereas keratinocytes showed a round shape on both membranes. hPDLF adhesion was greater oil P(VDF-TrFE)/BT at 2 and 4 h, while keratinocyte adhesion was similar for both membranes. Whereas proliferation was significantly higher for hPDLF on P(VDF-TrFE)/BT at days 1 and 7. no signs of keratinocyte proliferation could be noticed for both membranes Total protein content was greater on P(VDF-TrFE)/BT at 7, 14 and 21 days, and higher levels of ALP activity were observed oil P(VDF-TrFE)/BT at 21 days. Real-time PCR revealed higher expression of phenotypic markers of hPDLF and keratinocytes as well as greater expression of apoptotic genes in cultures grown on P(VDF-TrFE)/BT. These results indicate that, by favoring hPDLF adhesion. spreading. proliferation and typical mRNA expression, P(VDF-TrFE)/BT membrane should be considered an advantageous alternative for GTR (C) 2009 Acta Materialia Inc Published by Elsevier Ltd All rights reserved
Keywords: Cell culture; Fibroblast; Guided tissue regeneration; Keratinocyte; Membrane